Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11523-015-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of microRNA-21 and microRNA-221 in tumor-initiating stem-like cells modulates tumorigenesis, metastasis, and chemotherapy resistance in pancreatic cancer

Abstract: Our preliminary studies identified a small population side population (SP) cells in pancreatic cancer cells with stem cell-like properties, which were able to induce fast and aggressive tumor formation in nude mice. Gene expression analysis showed a significant difference in the expression of more than 1,300 genes in SP cells, among which a highly significant difference in microRNA expression of miR-21 and miR-221 between SP and NSP cells was identified. SP cells were identified and characterized by flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…Our observation that miR-21 overexpression leads to faster tumor growth in a nude mouse xenograft model is consistent with a report that inhibiting miR-21 in pancreatic CSCs substantially decreased the growth of pancreatic tumor xenografts [42]. In another study, colorectal cancer cells were stably transfected with miR-21 plasmid and subcutaneously injected into female SCID mice [43].…”
Section: Discussionsupporting
confidence: 91%
“…Our observation that miR-21 overexpression leads to faster tumor growth in a nude mouse xenograft model is consistent with a report that inhibiting miR-21 in pancreatic CSCs substantially decreased the growth of pancreatic tumor xenografts [42]. In another study, colorectal cancer cells were stably transfected with miR-21 plasmid and subcutaneously injected into female SCID mice [43].…”
Section: Discussionsupporting
confidence: 91%
“…For miR-21 and miR-122, ASOs increase the levels of their targets (PTEN, BCL2, RECK and CDKN1B), reduce proliferation and increase apoptosis of pancreatic cancer cells. In addition, they sensitize PDAC cells to gemcitabine [20,35,39].…”
Section: Mirna and Pancreatic Diseases: Diagnosis Prognosis And Thermentioning
confidence: 99%
“…Hence, emerging studies have discovered that the differential expression of miRNA, such as miR-21, miR-99a, and miR-34a, could predict the prognosis of PaCa patients [16][17][18]. In pancreatic tumor tissue, aberrant expression of miRNAs, such as miR-21, miR-221, miR-34a, and miR-217, were reported, which suggested that these molecular regulators had the potential to serve as biomarkers [17,[19][20][21]. Meta-analyses were conducted to evaluate the diagnostic value of miRNAs, and they showed moderate predictive values for PaCa diagnosis [22,23].…”
Section: Introductionmentioning
confidence: 99%